2017
DOI: 10.1080/03601234.2017.1293457
|View full text |Cite
|
Sign up to set email alerts
|

Detection of antibiotics in chicken eggs obtained from supermarkets in Ho Chi Minh City, Vietnam

Abstract: The residual levels of antibiotics in Vietnamese eggs were monitored from 2014 to 2015. A total of 111 egg packages, distributed by 11 different companies, were collected from supermarkets in Ho Chi Minh City and the levels of 28 antibiotics were analyzed using liquid chromatography-tandem mass spectrometry (LC-MS/MS) screening method. Sixteen samples tested positive for antibiotics; a total of eight compounds (enrofloxacin, ciprofloxacin, norfloxacin, sulfadimethoxine, sulfamethazine, sulfamonomethoxine, tilm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 13 publications
3
18
0
1
Order By: Relevance
“…Stricter legislation on antimicrobial use may be seen as a positive step in the global fight against AMR, which, to be truly effective, requires the development of enforcement capacity. For example, despite a more extensive infrastructure and tighter control over antimicrobial use in Thailand, researchers have described black market and illegal use of antimicrobials in livestock [58,59], while antimicrobial residues have been identified in eggs and meat from retail outlets in Vietnam despite regulation of maximum residue limits [60,61]. In addition, the case studies identified that farmers were reluctant to adopt new legislation.…”
Section: Resultsmentioning
confidence: 99%
“…Stricter legislation on antimicrobial use may be seen as a positive step in the global fight against AMR, which, to be truly effective, requires the development of enforcement capacity. For example, despite a more extensive infrastructure and tighter control over antimicrobial use in Thailand, researchers have described black market and illegal use of antimicrobials in livestock [58,59], while antimicrobial residues have been identified in eggs and meat from retail outlets in Vietnam despite regulation of maximum residue limits [60,61]. In addition, the case studies identified that farmers were reluctant to adopt new legislation.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, research was also conducted with other food such as eggs. Various antibiotics were detected in chicken eggs sold in supermarkets in Ho Chi Minh city (Yamaguchi et al , 2017). A total of 111 egg packages from 11 different companies were examined for 28 different antimicrobials, and 16 samples were positive for any of eight compounds (enrofloxacin, ciprofloxacin, norfloxacin, sulfadimethoxine, sulfamethazine, sulfamonomethoxine, tilmicosin, and tripthoprim).…”
Section: Residual Antimicrobial In Various Foods and Environmental Wamentioning
confidence: 99%
“…Some other studies conducted in other provinces such as Bac Giang, the Red River Delta (Ha Noi Capital City, Hai Duong, and Thai Binh provinces), the Mekong Delta, Ho Chi Minh City, or Nha Trang City also showed that these antibiotic groups were commonly used. [4][5][6]8,11 Studies in other countries such as China, Thailand, Turkey, EI-Sharkia Governorate, and Lebanon have also found that more commonly used antibiotics were tetracycline, fluoroquinolones, and sulfonamides. [12][13][14][15][16] This result showed that the detection of many samples containing the residues of fluoroquinolones, tetracycline, and sulfonamides reconfirmed the situations reported in other provinces and other countries.…”
Section: Antibiotic Residues In Chicken Meatmentioning
confidence: 99%
“…Despite limited research on this problem in Vietnam, qualitative studies have reflected the actual use of antibiotics in livestock production, such as the survey in 2013 in Ho Chi Minh City and in Binh Duong province in 2002 showed 17.3% and 47% chicken samples with antibiotic residues. 4,5 The demand for food is growing and livestock production is also increasing, while the area of livestock production has shrunk, which makes disease control more complicated. Chau Thanh district has the largest number of chicken farms (40%) in the Tay Ninh province, which served as the main source of broiler meat for the whole province and surrounding areas.…”
Section: Introductionmentioning
confidence: 99%